Chlamydia pneumoniae (TWAR) in Atherosclerosis of the Carotid Artery - Grayston, J. Thomas; Kuo, Cho-chou; Coulson, Alan S.; Campbell, Lee Ann; Lawrence, Robert D.; Lee, Ming Jong; Strandness, Eugene D.; Wang, San-pin (Circulation (New York, N.Y.), 1995)
Background Chlamydia pneumoniae has been demonstrated in atherosclerotic lesions of coronary arteries and aorta. A seroepidemiological study found C pneumoniae –specific antibody more frequently in persons with significant carotid artery wall thickening than in matched control subjects. Methods and Results Fresh-frozen or formalin-fixed tissue obtained at carotid endarterectomy was examined by immunocytochemistry (ICC) and the polymerase chain reaction (PCR) for the presence of C pneumoniae. Five of five fresh-frozen and formalin-fixed carotid endarterectomy specimens were positive for C pneumoniae by ICC (three of five by PCR). A total of 56 archival formalin-fixed, paraffin-embedded carotid endarterectomy tissues from three hospitals were examined by ICC. Thirty-two were positive. Thirteen normal carotid artery tissue sections from six patients were negative for C pneumoniae . Conclusions C pneumoniae organisms are frequently found in the advanced carotid atherosclerotic lesions of persons undergoing endarterectomy. Although these findings do not establish causality for C pneumoniae in carotid artery atherosclerosis, they should stimulate investigation of a possible causal or pathogenic role for the organism in the disease.